Estudos aplicados ao uso da Moringa Oleifera como coagulante natural para melhoria da qualidade de águas - Silva, Cleuza Aparecida da (2005)
The purpose of this study was to use of Moringa oleifera seeds as an alternative coagulant for water treatment. The M. oleifera seeds were obtained from cultivated plants in Campus Umuarama of Federal University of Uberlândia (Uberlândia/MG). The moringa extracts were prepared mixing 10.0 grams of powder of seeds in 200 mL of water and agitation by 90 minutes. Measurements of pH, conductivity, turbid and total solids were made after and before water treating with M. oleifera seeds. In this case, 15.0 mL of 50 g.L'1 extract were mixing in water and agitated by 5 minutes in 400 rpm and 15 minutes in 200 rpm. Studies involving concentration coagulant, time and temperature of extraction step and pH were made to optimise the conditions to removal turbidity of water samples. Extracts shown to ha ve large effects on turbidity removal (92-96% reduction). The feasibility of water treatment process for fluoride removal also has been evaluated. Fluoride ions were removed from a solution using 10.0 mL of moringa extract on the 50.0 g.L=1 concentration. In this condition, the removal of fluoride was 100%. The data shown that the M. oleifera is an effective natural coagulant which can be used in water treatment. Additionally, the using coagulants derived from Moringa oleifera seeds shown to be feasible for treating water, a low cost procedure, provide alternative procedure of treatment water for communities that not have treating water and also reduce potential heath hazards from Chemical overdosing of traditional coagulants.